2007
DOI: 10.1038/sj.bjp.0707304
|View full text |Cite
|
Sign up to set email alerts
|

Localization of intracellular compartments that exchange Na,K‐ATPase molecules with the plasma membrane in a hormone‐dependent manner

Abstract: Background and Purpose: Dopamine is a major regulator of sodium reabsorption in proximal tubule epithelia. By binding to D1‐receptors, dopamine induces endocytosis of plasma membrane Na,K‐ATPase, resulting in a reduced capacity of the cells to transport sodium, thus contributing to natriuresis. We have previously demonstrated several aspects of the molecular mechanism by which dopamine induces Na,K‐ATPase endocytosis; however, the location of intracellular compartments containing Na,K‐ATPase molecules has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
(81 reference statements)
1
19
0
Order By: Relevance
“…These circulating hormones can exert either short term or long term regulation on Na ϩ /K ϩ -ATPase via changing the gene expression level, reversible phosphorylation of its subunits, or modulating its trafficking (14,15). Recently, accumulated evidence indicates that estrogen has a great effect on the activity and expression of Na…”
Section: Namentioning
confidence: 99%
“…These circulating hormones can exert either short term or long term regulation on Na ϩ /K ϩ -ATPase via changing the gene expression level, reversible phosphorylation of its subunits, or modulating its trafficking (14,15). Recently, accumulated evidence indicates that estrogen has a great effect on the activity and expression of Na…”
Section: Namentioning
confidence: 99%
“…The second mechanism of regulation is that new Na C /K C -ATPase subunits are delivered to the plasma membrane from intracellular stores when needed (Hundal et al 1992, Al-Khalili et al 2003. It has been shown that Na C /K C -ATPase-containing compartments are located just underneath the plasma membrane (Efendiev et al 2007). Regulation performed through direct effects on the kinetic behavior of the enzyme occurs within minutes to hours and is accomplished through changes in the turnover rate of the existing pumps via the phosphorylation of protein kinase A (PKA), PKC, PKB, or PKG ( Fig.…”
Section: Regulation Of Namentioning
confidence: 99%
“…The isoforms combine to form a number of Na C /K C -ATPase isozymes expressed in a tissue-specific and cell-specific manner (Jorgensen et al 2003). The heterodimeric protein subunits are synthesized independently in the endoplasmic reticulum and assembly during or very soon after synthesis in this organelle (Geering et al 1996, Therien & Blostein 2000, Efendiev et al 2007.…”
Section: Structure and Functionmentioning
confidence: 99%
“…In nontreated cells, NKA ␣1 is mostly localized in the plasma membrane region, and AP-1 is in cytosolic regions surrounding the nucleus. We have previously demonstrated that the intracellular compartments containing NKA molecules are close to the plasma membrane and that it is difficult to distinguish between NKA molecules that are at the plasma membrane and in intracellular compartments (38). In cells treated with Ang II, it can be observed that AP-1 molecules have been recruited to the plasma membrane region where the NKA-containing intracellular compartments are located, and consequently the level of FRET N between the fluorophores attached to NKA and AP-1 has been significantly increased (arrows on Fig.…”
Section: Resultsmentioning
confidence: 99%